Strategic Assessment of Evapotranspiration for Wheat Cultivation in Punjab, Pakistan - Hussain, Syed Zaheer; Zubair, Maria; Awan, Arsam Ahmad (Journal of Public Policy Practitioners, 2025)
The nation’s main wheat producing area, namely the province of Punjab, is becoming progressively more susceptible to water constraints brought on by climate change, ineffective irrigation techniques, and inadequate management of water for agriculture. The lack of district-level evapotranspiration (ET) surveillance networks, which are necessary for developing an appropriate water policy, exacerbates these difficulties. The absence of geographically and statistically specified ET data for optimal irrigation planning during wheat farming is an important regulatory gap that this investigation covers. For the 2022-2023 season, the study evaluates ET throughout the five major phenological phases of wheat (sowing, tillering, flowering, grain filling, and harvesting), utilizing Sentinel-2 satellite images and Google Earth Engine. A vegetation-index-driven ET computational method is used to produce high-resolution maps and district-level evaluations that represent variations in water demand within and between seasons. The results show notable spatial differences between districts like Faisalabad and Bahawalpur, with ET peaking at the grain filling stage ( 4.09mm/day) and falling during sowing ( 1.95mm/day). Presenting a data driven framework for proportionate water distribution, regional irrigation zoning laws, and climate-resilient agrarian management, this study offers plenty to the larger legislative conversation. It makes the case that incorporating remote sensing into policies can improve the allocation of resources and productivity, two essential components of sustainable agriculture strategies in the face of increasing environmental stress.